Predictors of Pregnancy Outcome for Libyan Infertile Women Underwent Intracytoplasmic Sperm Injection Cycle at Tripoli Infertility Center - Abdulabasit Afhayl Alboum; Amal Sulaeman; Eshraq Alsherif (AlQalam Journal of Medical and Applied Sciences, 2024)
Intracytoplasmic Sperm Injection (ICSI) is a crucial treatment approach in assisted reproduction technology (ART) for infertility clinics. However, low pregnancy rates in ICSI cycles are a problem. Despite its potential, ICSI can be expensive, time-consuming, and cause concerns about gametes and newborn health. The study aims to identify factors predicting pregnancy rates among infertile couples undergoing Intracytoplasmic Sperm Injection cycle at Tripoli Infertility Center in Libya. This retrospective study reviewed all infertile couples’ medical files at the Infertility Tripoli Centre from January to December 2023. A structured case sheet was used to collect data on female patients’ age, causes of infertility, duration of infertility, previous pregnancy, antral follicles count, endometrial thickness, number of embryos transferred, and pregnancy outcomes. The study was divided into two groups based on pregnancy test results. Statistical analysis involved simple descriptive statistics, Chi square, and independent sample t-test. This study involved 90 women, with 35.6% having a positive pregnancy test. The pregnancy rate was 59.4% in women under 35, and decreased to 9.4% in those 40 or older. No significant differences were found in infertility duration or previous pregnancy (all P > 0.05). Partner analysis revealed that 64.2% had asthenospermia, while endocrinopathies were reported by 41.8% of women. No significant differences were found in antral follicle count, endometrial thickness, oocyte number, or quality between pregnant and non-pregnant women (all P > 0.05). Our findings suggest that Maternal age has a significant impact on the success of ICSI, with advanced age in women negatively affecting ICSI outcomes. الحقن المجهري هو نهج علاجي حاسم في تقنية المساعدة على الإنجاب. ومع ذلك ، فإن انخفاض معدلات الحمل في دورات الحقن المجهري يمثل مشكلة. على الرغم من إمكاناته ، يمكن أن يكون الحقن المجهري مكلفا ويستغرق وقتا طويلا ويسبب مخاوف بشأن الأمشاج وصحة الأطفال حديثي الولادة. الهدف من الدراسة هو تحديد العوامل التي تتنبأ بمعدلات الحمل بين الأزواج المصابين بالعقم الذين خضعوا لدورة الحقن المجهري في طرابلس . استعرضت هذه الدراسة بأثر رجعي جميع الملفات الطبية للأزواج المصابين بالعقم في مركز العقم في طرابلس من يناير إلى ديسمبر 2023. تم استخدام استبيان لجمع البيانات حول عمر المريضات ، وأسباب العقم ، ومدة العقم ، والحمل السابق ، وعدد الجريبات الغارية ، وسمك بطانة الرحم ، وعدد الأجنة المنقولة ، ونتائج الحمل. تم تقسيم الدراسة إلى مجموعتين بناء على نتائج اختبار الحمل. تضمن التحليل الإحصائي إحصاءات وصفية بسيطة ، ومربع كاي ، واختبار ت للعينة المستقلة.شملت هذه الدراسة 90 امرأة ، كان الحمل إيجابيا في 35.6٪منهم. كان معدل الحمل 59.4٪ لدى النساء دون سن 35 عاما ، وانخفض إلى 9.4٪ في سن 40 أو أكثر. لم يتم العثور على فروق ذات دلالة إحصائية في مدة العقم أو الحمل السابق (P > 0.05). كشف تحليل الزوج أن 64.2٪ يعانون من وهن النطاف ، بينما تم الإبلاغ عن اعتلالات الغدد الصماء من قبل 41.8٪ من النساء. لم يتم العثور على فروق ذات دلالة إحصائية في عدد الجريبات الغارية أو سمك بطانة الرحم أو عدد البويضات أو الجودة بين النساء الحوامل وغير الحوامل (جميعها P > 0.05). تشير النتائج التي توصلنا إليها إلى أن عمر الأم له تأثير كبير على نجاح الحقن المجهري ، حيث يؤثر تقدم العمر لدى النساء سلبا على نتائج الحقن المجهري